Contamination of aluminium from cooking utensils and yogurt containers - Yaman, M; Günes, M; Bakirdere, S (Springer-Verlag, 2003)
[Abstract Not Available]
Keywords: Atomic-Absorption Spectrometry; Activated-Carbon Enrichment; Speciation; Fruits; Lead; Preconcentration; Vegetables; Soils; Vanadium; Matrices